PENELUSURAN HUBUNGAN ANTARA MODULUS TANAH DASAR DENGAN NILAI CBR - Ibnu Sabil, Ronni
Abstract : ASSESSMENT OF RELATIONSHIP BETWEEN.SUBGRADE MODULUS AND CBR TEST, Ronni Ibnu Sabil, 1993, Program Sistem dan Teknik Jalan Raya, Program Pendidikan Magister, Program Pasca Sarjana, Institut Teknologi Bandung. In the empirical design approach, California Bearing Ratio (CBR) values are widely used to characterize the subgrade strength for pavement design input while, in an analytical approach, the-soil strength is expressed in terms of resilient modulus. The resilient modulus can be obtained from special triaxial testing, which has not been widely used in pavement ,design work. Apparatus availability and cost of testing are the usual constraints on resilient modulus determination. The other elastic modulus used to specify the elastic response of a soil is found from constant rate loading in unconsolidated undrained triaxial testing in the laboratory. The general objective of this thesis has been to assess the relationship between the subgrade modulus, expressed in terms of the unconsolidated-undrained elastic modulus of a, soil and CBR value as found in unsoaked laboratory CBR\',-testing. The result of the study indicated that the relationship between subgrade modulus and CBR value could be represented by power function models. The spread of. laboratory test data over the obtained mathematical models were found to closely resemble the California Bearning Ratio - resilient modulus relationship as proposed by Heukelomp and Klomp (1964). It was found that there was a relationship between the unconsolidated undrained triaxial modulus with static loading at constant rate and resilient modulus as obtained in a dynamic loading triaxial test. An approximation is therefore suggested in order to find subgrade elastic parameters from the result of unconsolidated undrained Triaxial testing at several values of confining pressure, in line with real loading conditions.